Acute effect of cola and caffeine on locomotor activity in drosophila and rat - Kmeťová, Katarína; Maronek, Martin; Borbélyová, Veronika; Hodosy, Július; Celec, Peter (Physiological research, 2021)
Caffeine is well known for reducing fatigue and its effect on behavior is widely studied. Usually, caffeine is not ingested in its pure form but rather in sugar-sweetened beverages such as cola. Our aim was to compare the acute effect of cola and caffeine on locomotor activity. Rats and flies ingested cola or caffeine solution for 24 hours. The open field test revealed higher locomotor activity in cola groups for both flies and rats. Surprisingly, no differences have been observed between caffeineand control group. We conclude that caffeine itself does not explain the effect of cola on locomotor activity. Effect of cola cannot be generalized and interpreted for any caffeinated drink with other contents. Rather, the observed effect on locomotor activity may be caused by interaction of caffeine with other substances present in cola.
Keywords: Animals; Caffeine; sycené nápoje; Time Factors; časové faktory; Open Field Test; stimulanty centrálního nervového systému; kofein; lokomoce; zvířata; Locomotion; Central Nervous System Stimulants; test otevřeného pole; Carbonated Beverages; Drosophila melanogaster